Coupling behavior between lattice dynamics and Li self-diffusion in layered α-LiAlO2 ceramic. Issue 10 (15th May 2021) - Hu, Qiwei; Ma, Shenggui; Fang, Leiming; Xia, Yuanhua; Lei, Li; Kan, Wang Hay; Sun, Guangai; Peng, Shuming
Abstract: In molten carbonate fuel cells (MCFC), α -LiAlO2 ceramic matrix, at higher temperature or H-rich atmosphere, undergoes an irreversible phase transition of α -LiAlO2 to γ -phase that causes a large volume change and greatly impacts the lifetime of the cells. In this manuscript, we unravel an unusual coupling property between the lattice dynamic and Li + ions diffusion for the first time, near the common operating temperature of 923 K. A temperature-dependent lattice dynamics study on α -LiAlO2 was performed by probing the in-situ Raman spectroscopy. In addition, the phonon density of states was estimated theoretically through first-principles calculations. Notably, in-situ Raman spectroscopy combined with the calculated atom-projected phonons density of states (PDOS) and Bond Valence Energy Landscape (BVEL) calculations demonstrated that the phonon mode Eg dominated by oxygen atoms decays into three acoustical phonons that couple with the diffusion of mobile Li + ions in ab -plane above 600 K. In MCFC environments, large amounts of Li + ions or H + ion in the electrolyte will diffuse into the lattice of α -LiAlO2 . This would further enhance the coupling behavior between oxygen atoms and diffusion ion and finally results in the instability of lattice dynamics of oxygen atoms.